“THE JEWISH QUESTION” IN THE PAGES OF CONTIMPORANUL - Emilia FAUR (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
The Jewish Question in the Pages of Contimporanul. It is my interest to investigate how one of the Romanian leading interwar avant-garde magazines, Contimporanul (1922-1932), tackled the Jewish question. In this respect, I will consider the various standpoints the contributors took on the matter, presenting it in all its facets and complexity, as both a political and a cultural phenomenon. The analysis of the numerous articles covering the Jewish question, its causes and consequences, is meant to illustrate the sensibility Contimporanul demonstrates in regard to the Jewish question. Finally, I will conclude that, as in all matters covered, the magazines’ ideological position is democratic – For its contributors’ main claim is that the young Romanian state should prove itself to be united, modern, democratic based on the principles of integration and plurality, and not a nation-state based on ethnic and religious discrimination.